Exploring internal business factors and their impact on firm performance: Small business perspective in Ethiopia - Abriham Ebabu Engidaw (Journal of Innovation and Entrepreneurship, 2021)
Mainly, the study is aimed at exploring the internal business factors and their impact on firm performance in micro- and small-scale enterprises. The study employed a descriptive and explanatory research design and used a quantitative research approach. The study is conducted on Amhara region, North Wollo zone, Lalibela city administration micro- and small-scale enterprise operators, and in this study, the dependent variable is the performance of SMEs while independent variables are managerial factors, workplace factors, and entrepreneurial factors. To achieve the objectives of the study, 199 sample micro and small enterprises are selected from the 395 target populations. It used an explanatory design with stratified and simple random sampling techniques. The study employed descriptive and inferential statistical data analysis methods. The finding shows that the independent variables managerial factors and workplace-related factors have a positive and significant effect on small business performance in the study area. Also, there is an insignificant relationship between entrepreneurial factors and the dependent variable.
Keywords: 650; Entrepreneurial factors; Managerial factors; Small business performance; Workplace factors